PERAN ORANG TUA DALAM MEMBANGUN KARAKTER ANAK USIA SEKOLAH DASAR DI MI AL-IHSAN KEBONAGUNG MALANG - Alizza Fikriyyah Wardani; Mohammad Afifulloh; Devi Wahyu Ertanti (JPMI: Jurnal Pendidikan Madrasah Ibtidaiyah, 2022)
The background of this research is, looking at the times that are constantly developing and affecting the physical, mental, and character growth of a child. This research was conducted at a school in a suburban or rural area of Sememek, Kebonangung, Malang. more precisely at MI Al-Ihsan Kebonagung Malang. where the researcher wants to know the role of parents in building the character of children at elementary school age at the school. This research was conducted using qualitative methods with observations and interviews with several parents and children. In the study, what efforts were made by parents to build and also to develop character in children at the age of the child at the elementary school (SD) level which still really needs father and mother figures as parents in the family scope. As well as factors that support in building and developing children's character at elementary school age (SD). So that the formation of an educated and programmed generation. And in terms of behavior, attitudes and behavior as well as spoken words do not hurt others or make them a more civilized human being, especially at the age that is still at the elementary school level.Keywords: parents, role of parents, building, children's character